Novel leaderless bacteriocin geobacillin 6 from thermophilic bacterium Parageobacillus thermoglucosidasius - Koniuchovaitė, Ana; Petkevičiūtė, Akvilė; Bernotaitė, Emilija; Gricajeva, Alisa; Gegeckas, Audrius; Kalėdienė, Lilija; Kaunietis, Arnoldas (Frontiers in Microbiology, 2023)
Bacterial resistance to conventional antibiotics has urged us to develop alternative strategies against bacterial pathogens. Moreover, a demand for food products containing no chemical preservatives have led us to search new alternative technologies for food preservation. Bacteriocins – ribosomally synthesized antimicrobial peptides have been proposed as a new alternative to conventional antibiotics or chemicals for food preservation. This study describes biosynthesis and characterization of a novel leaderless bacteriocin, geobacillin 6, which was identified in thermophilic bacterium Parageobacillus thermoglucosidasius. Its amino acid sequence shows low similarity to other bacteriocins and it is the first leaderless-type bacteriocin identified in thermophilic bacteria. Based on structure assessment, the bacteriocin forms a multi-helix bundle. Geobacillin 6 exhibits a relatively narrow antimicrobial spectrum, it is active in µM range and against Gram-positive bacteria, mostly thermophilic species closely related to the producer strain. Bacteriocin demonstrates stability over pH 3-11 and is highly thermostable, retaining 100% of its activity after incubation at 95°C for 6 hours. Geobacillin 6 has potential in food industry and biotechnological processes where contamination with thermophilic bacteria is undesirable.